The role of FDI in the sustainable development of the European Union - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2023)
This paper aims to examine the role of international business behavior in the sustainable development of the European Union (EU) and to answer two questions: (1) To what degree could international business contribute to the development of a "green economy" under the uncertainty caused by the COVID-19 pandemic?; (2) In what way could host countries attract "green" and socially responsible foreign direct investment (FDI)? The statistical analysis of international business involvement in environmentally harmful sectors/industries of the EU economy indicates that the share of such investments in most member states did not exceed 20% of the total FDI stocks between 2015 and 2020. The structure of investments changed in half of the analyzed countries towards sectors/industries that were less harmful to the environment. These changes and high requirements for domestic and foreign companies within the framework of the EU's environmental policy allow us to conclude that international business contributed to the ecological transformation of the EU. On the other hand, changes in the structure of FDI stocks located abroad by the EU Member States in environmentally harmful sectors/industries were multidirectional. Six of the EU states remained net exporters of direct investment in these sectors/industries. The involvement of foreign direct investors in the new EU Member States in sectors that are important for implementing the Sustainable Development Goals (SDGs) of the 2030 Agenda was not very high. It was characterized by high volatility and did not play a significant role in their economies. Attracting "green FDI" and socially responsible investments requires changes in policy towards foreign investors. They should include facilitating foreign investment, including investments aimed at sustainable development, incentives for investors to engage in "green investments", and making investment agreements more flexible to combat climate change.
Keywords: F01; F23; F64; 330; foreign direct investment; sustainable development; European Union; ecological issues